History and treatment of a neurosis - Female Homosexuality and characterological complex linked to oral eroticism - Gutiérrez Noriega, Carlos (2014)
We report in this study the results of the investigation of a neurosis following psychoanalytic technique. As when dealing with any neurosis it must necessarily touch on the subject of infantile sexuality, we believed essential inserting before the presentation of the case, a summary thereof, relating to the extent possible, with the neurophysiological organization of the child. In this effort, we recognize it in advance, we have only managed sketching, and imperfectly, some basic facts and some working hypotheses. The problem is very complicated.